Dynamic response of the horizontal stabilizer during UAS airborne collision. (April 2019) - Meng, Xianghao; Sun, Yingjun; Yu, Jingyu; Tang, Zhongbin; Liu, Jun; Suo, Tao; Li, Yulong
Highlights: Structural level drone collision ground test in accordance with real collision scenarios. Finite element model obtained through reverse engineering and validated by structural level test data. Hazard assessment of different drone airborne collision scenarios by validated computational model. Abstract: An airborne collision between civil Unmanned Aerial Systems (UASs) and manned aircraft is a potential threat to the aircraft operation safety. In this paper, a structure level UAS collision ground test was performed on a commercial airliner horizontal stabilizer section to investigate the dynamic response of this primary operation component. The projectile was a 3.4 kg quadcopter named 'Inspire I'. Explicit dynamic code PAM-CRASH R was employed to simulate the collision process and the modeling procedures were modified through comparison with test data, followed by series of simulations to assess the hazard of different collision scenarios. The results showed that 3.4 kg drone impact at the airliner cruising speed could cause some damage on the horizontal stabilizer front spar and the situation is more serious than 3.6 kg bird strike in which the hardness of drone components rather than kinetic energy is a decisive factor. The lithium-ion battery penetrated into the airframe had a smoke sign in the test, which might be a potential ignition source.